1995
DOI: 10.1111/j.1524-4725.1995.tb00281.x
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Early Malignant Transformation in a Spiradenoma

Abstract: We ascribe the early detection of this tumor to increased public awareness of the importance in seeking early treatment of skin lesions. Histologic examination of this stage may eventually outnumber the now more commonly described latter stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…The precise identification of a benign or malignant hidradenoma, based on pathological examination, was not possible. Similar findings were noted in other case reports of clear cell hidradenoma [21][22][23][24][25][26] .…”
Section: Discussionsupporting
confidence: 92%
“…The precise identification of a benign or malignant hidradenoma, based on pathological examination, was not possible. Similar findings were noted in other case reports of clear cell hidradenoma [21][22][23][24][25][26] .…”
Section: Discussionsupporting
confidence: 92%
“…In the histopathologic examination of MES, two distinct components are seen: typical benign eccrine spiradenoma and carcinoma with areas of transitions 8 . The carcinoma may show squamous differentiation or sarcomatous change 1,7,14 . Microscopic examination in our case showed only carcinoma, including proliferation of solid masses of tumor cells with large hyperchromatic nuclei and frequent atypical mitoses, invasion of surrounding connective tissue, loss of basement membrane, and squamous differentiation.…”
Section: Discussionmentioning
confidence: 50%
“…These results are similar to other studies reviewing spiradenocarcinoma from all cutaneous sites. Herzberg et al 13 found local recurrence and metastasis rates at 32% and 44%, respectively, with a disease-specific mortality of 20%. 13 A more recent review placed local recurrence and metastasis rates at 57% and 39%, respectively, with a disease-specific mortality of 39%.…”
Section: Discussionmentioning
confidence: 97%
“…Herzberg et al 13 found local recurrence and metastasis rates at 32% and 44%, respectively, with a disease-specific mortality of 20%. 13 A more recent review placed local recurrence and metastasis rates at 57% and 39%, respectively, with a disease-specific mortality of 39%. 5 Although control of disease has been shown after reexcision of local recurrence, once distant metastasis occurs, death ensues rapidly.…”
Section: Discussionmentioning
confidence: 97%